Investigation of pedestrian-level wind environment near two high-rise buildings in different arrangements. Issue 12 (September 2019) - Mittal, Hemant; Sharma, Ashutosh; Gairola, Ajay
The presence of buildings that surround the wind environment adversely affects at the pedestrian level. The present study investigates the effect of different arrangement of two buildings on wind flow structure and modification of wind speed conditions at the pedestrian level. The investigation was carried out for parallel, tandem, and staggered arrangement of two buildings using computational fluid dynamics simulations. The wind tunnel experiments were conducted to validate the computational fluid dynamics results. The computational fluid dynamics simulations were performed using the standardk − ε model with LK modification and revised closure coefficients. Different flow features such as skew-symmetric vortex structure for parallel arrangement, reattachment of shear layer on the surfaces of the downstream building for tandem arrangement, and deviation of wake region behind the upstream building to leftward of the flow direction for staggered arrangement were observed. It was observed that the strong wind conditions were mostly affected by tandem and parallel location of the twin buildings. The results of numerical simulation obtained using the modified SKE model were found to be in good agreement with the experimental results.